A novel 2q37 microdeletion containing human neural progenitors genes including STK25 results in severe developmental delay, epilepsy, and microcephaly. (4th August 2015) - Imitola, Jaime; Khurana, Divya S.; Teplyuk, Nadiya M.; Zucker, Mark; Jethva, Reena; Legido, Agustin; Krichevsky, Ana M.; Frangieh, Michael; Walsh, Christopher A.; Carvalho, Karen S.
<x xml:space="preserve">Abstract</x> 2q37 microdeletion syndrome is a rare syndrome characterized by neurodevelopmental delay, bone, cardiovascular, and neurological alterations. This syndrome is typically associated with loss of genetic material of approximately 100 genes in the 2q37 band. However, the genes associated with neurodevelopmental phenotype in this syndrome are still unknown. We identified a deleted region of 496 kb by whole genome array CGH in a patient who fulfilled criteria for 2q37 microdeletion syndrome with developmental delay, microcephaly, hypoplasia of the corpus callosum, hand wringing, toe walking, and seizures. The deleted segment contains genes that are highly expressed in the developing human cortical plate and the subventricular zone (SVZ) in vivo and human neural progenitors in vitro, including SEPT2, THAP4, ATG4B, PPP1R7, and STK25. Network analysis revealed that STK25 was the most interacting gene associated with neural development in this deletion. Our report narrows the likely causative genomic region for microcephaly and neurodevelopmental delay in 2q37 microdeletion syndrome to a small genomic region enriched with neural progenitor genes that may represent an important locus for the development of the human cortex and corpus callosum. © 2015 Wiley Periodicals, Inc.